Rileggere “Class Counts” di Erik Olin Wright: attualità di un classico contemporaneo del marxismo scientifico - Bellini, Andrea (Cambio. Rivista sulle Trasformazioni Sociali, 2021)
Two years after Erik Olin Wright’s death, this article rereads one of his most famous works, Class Counts. This book, published in 1997, can be considered at the same time a contemporary classic of scientific Marxism and the manifest of neo-Marxist class analysis. The objectives of the article are manifold. Firstly, it contextualizes the author’s theoretical contribution in his biography, emphasizing his complicated relationship with sociology as a Marxist. Then, it focuses on the book’s specific contribution in terms of conceptual work, also looking at the theoretical implications of the empirical results. Finally, it reflects on the resilience of the heuristic capacity of Wright’s categories to understand social inequalities in contemporary society.